A computational enhancement of Base64 algorithm using Residue Number System algorithms - LOGUNLEKO, Kolawole Bariu; LOGUNLEKO, Abolore Muhamin; ASAJU-GBOLAGADE, Ayisat Wuraola; BABATUNDE, Akinbowale Nathaniel; GBOLAGADE, Kazeem Alagbe (Revista română de informatică și automatică = Romanian journal of information technology and automatic control, 2025)
Today's daily existence depends heavily on the advancement of data, information and communication technologies. Consequently, there is a huge increase in the need for data and information. In communicating data over a public network, data security is a necessity that must be carefully taken into consideration. Thus, Base64 algorithm has been used in numerous security applications for ensuring data confidentiality, integrity and authentication. However, research shows that there are security vulnerabilities in the most widely used Base64 algorithm due to the absence of a key mechanism. To address this concern, the research employs residue number system algorithms for the enhancement of the Base64 algorithm because of its cryptographic features and thereby strengthens the transformation of the existing Base64 algorithm to produce a novel symmetric-based cryptographic algorithm. The developed algorithm generates a symmetric key by shuffling the original key with the textual data, making the transformation of each character of the data better each time it is shuffled. Therefore, the research bridges the security gap in the Base64 cryptographic algorithm by factoring the key mechanism of the RNS based algorithm into the newly developed algorithm. The pattern and confusion produced during the methodology procedure safeguards the data more effectively as shown in the cipher text generated.